2005
DOI: 10.1159/000087097
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mild Stress (CMS) Revisited: Consistency and Behavioural-Neurobiological Concordance in the Effects of CMS

Abstract: The chronic mild stress (CMS) model of depression has high validity but has in the past been criticized for being difficult to replicate. However, a large number of recent publications have confirmed that CMS causes behavioural changes in rodents that parallel symptoms of depression. This review summarizes studies from over sixty independent research groups that have reported decreases in reactivity to rewards, and a variety of other depression-like behaviours, in rats or mice, following exposure to CMS. Toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

74
1,042
4
47

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,445 publications
(1,167 citation statements)
references
References 311 publications
(155 reference statements)
74
1,042
4
47
Order By: Relevance
“…Chronic mild stress has been reported to induce an anhedonic-like state in rodents,that resembles the affective disorder phenotypes in humans [189]. In particular, Willner and colleagues originally reported that chronic and sequential exposure of rats or mice to a mild stress regimen caused decreases in responsiveness to rewards [190,191], commonly reported as a decrease in the consumption of and preference for sucrose solutions, and a decrease in the rewarding properties of pharmacological and natural rewards in the place preference behavioral paradigm [189,192-194]. The chronic stress paradigm is considered to have a greater etiological relevance and face validity in mimicking MDD than other animal models, and therefore has become one of the most widely used preclinical paradigms of affective disorders [195].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic mild stress has been reported to induce an anhedonic-like state in rodents,that resembles the affective disorder phenotypes in humans [189]. In particular, Willner and colleagues originally reported that chronic and sequential exposure of rats or mice to a mild stress regimen caused decreases in responsiveness to rewards [190,191], commonly reported as a decrease in the consumption of and preference for sucrose solutions, and a decrease in the rewarding properties of pharmacological and natural rewards in the place preference behavioral paradigm [189,192-194]. The chronic stress paradigm is considered to have a greater etiological relevance and face validity in mimicking MDD than other animal models, and therefore has become one of the most widely used preclinical paradigms of affective disorders [195].…”
Section: Reviewmentioning
confidence: 99%
“…Chronic mild stress causes significant reductions in absolute and relative sucrose intake in rats, that is associated with a decrease in striatal DA activity, and is reversed after chronic antidepressant administration with imipramine [196]. Decreased DA release to the NAc has been shown to occur after exposure to chronic repeated or an unavoidable stress regimen in rats [189,197,198], suggesting that stress significantly reduces mesolimbic DA transmission in rodent models. Altered DA function may also be related to changes in D 1 receptors, which have been shown to alter functional output in the rat limbic system after chronic unpredictable stress [199].…”
Section: Reviewmentioning
confidence: 99%
“…One of the depression-like behaviors in chronically stressed animals is reduction of sucrose preference, which is regarded as an analog of anhedonia, a key symptom of depression in human [12,13]. Systemic administration of leptin can reverse the chronic stress-induced decrease in sucrose preference [7].…”
Section: Animal Studiesmentioning
confidence: 99%
“…The biological significance of neuroticism-anxiety as a predictor of stress-related disorders is supported by a link between this personality trait and basal cortisol levels (Adler et al, 1997;Lindfors and Lundberg, 2002). Using the chronic unpredictable stress (CUS) model of depression (Willner, 1997(Willner, , 2005 in rats, we have identified an association between anxiety trait and both increased vulnerability to stress-induced depression-like symptoms and the response of the amygdala to emotional cues (Sandi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of animal models based on stress interventions have been shown to effectively mimic a variety of psychopathological alterations (Willner, 2005;Renthal et al, 2007;Stam, 2007;Ilin and Richter-Levin, 2009). In both animals and humans, excessive and/or enduring stress has been found to cause structural and neurochemical alterations in several brain structures, especially in the hippocampus (Lupien et al, 1998;Sheline et al, 1999;McEwen, 2000;Pham et al, 2003;Bisaz et al, 2011), the prefrontal cortex (Drevets et al, 1997;Rajkowska, 2000;Holmes and Wellman, 2009) and the amygdala (Sandi et al, 2008;Mitra et al, 2009;Roozendaal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%